Flow Volume Loop and Regional Ventilation Assessment Using Phase‐Resolved Functional Lung (PREFUL) MRI: Comparison With 129Xenon Ventilation MRI and Lung Function Testing. Issue 4 (27th November 2020) - Kaireit, Till F; Kern, Agilo; Voskrebenzev, Andreas; Pöhler, Gesa H; Klimes, Filip; Behrendt, Lea; Gutberlet, Marcel; Moher‐Alsady, Tawfik; Dittrich, Anna‐Maria; Wacker, Frank; Hohlfeld, Jens; Vogel‐Claussen, Jens
Abstract : Background: Regional flow volume loop ventilation‐weighted noncontrast‐enhanced proton lung MRI in free breathing has emerged as a novel technique for assessment of regional lung ventilation, but has yet not been validated with 129 Xenon MRI ( 129 Xe‐MRI), a direct visualization of ventilation in healthy volunteers, cystic fibrosis (CF), and chronic obstructive pulmonary disease (COPD) patients. Purpose: To compare regional ventilation and regional flow volume loops measured by noncontrast‐enhanced ventilation‐weighted phase‐resolved functional lung MRI (PREFUL‐MRI) with 129 Xe‐MRI ventilation imaging and with lung function test parameters. Study Type: Retrospective study. Population: Twenty patients with COPD, eight patients with CF, and six healthy volunteers. Field Strength/Sequence: PREFUL and 129 Xe‐MRI gradient echo sequences were acquired at 1.5T. Assessment: Coronal slices of PREFUL‐MRI (free breathing) and 129 Xe‐MRI (single breath‐hold) were acquired on the same day, matched by their ventrodorsal position and coregistered for evaluation. Ventilation defect percentage (VDP) was calculated based on regional ventilation (RV), regional flow volume loops (RFVL), or 129 Xe‐MRI with two different threshold methods. A combined VDP was calculated for RV and RFVL. Additionally, lung function testing was performed (such as the forced expiratory volume in 1 second [FEV1 ]) was used. Statistical Tests: The obtained parameters were compared using Wilcoxon tests, correlated using Spearman's correlation coefficient ( r ), and agreement between PREFUL and 129 Xe‐MRI parameters was assessed using Bland–Altman analysis and Dice coefficients. Results: VDP measured by PREFUL and 129 Xe were significantly correlated with both thresholding techniques ( r = 0.62–0.69, P < 0.05 for all) and with lung function test parameters. Combined RV and RFVL PREFUL defect maps correlated with lung function testing (eg, with FEV1 r = –0.87 P < 0.05), and showed better regional agreement to 129 Xe‐MRI ventilation defects (Dice coefficient defect 0.413) with significantly higher VDP values (10.2 ± 27.3, P = 0.04) than either PREFUL defect map alone. Data Conclusion: Combined RV and RFVL PREFUL defect maps likely increase sensitivity to mild airway obstruction with increased VDP values compared to 129 Xe‐MRI, and correlate strongly with lung function test parameters. Level of Evidence: 3 Technical Efficacy Stage: 2